2021
DOI: 10.1055/a-1443-5451
|View full text |Cite
|
Sign up to set email alerts
|

OCT Application for Sterile Corneal Graft Screening in the Eye Bank

Abstract: Background and Objective Sterile donor tomography enables the detection of corneal tissues with refractive anomalies. The aim of this study was to determine the curvature and thickness of donor corneas to support proper selection in the eye bank. Methods 704 donor corneas (Klaus Faber Center, LIONS Eye Bank Saar-Lor-Lux, Trier/Westpfalz, in Homburg/Saar) were measured using the anterior segment optical coherence tomograph (AS-OCT) CASIA 2 (Tomey Corp., Nagoya, Japan). The corneoscleral discs were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…16,17 Anterior Segment Optical Coherence Tomography has also been used to detect curvature abnormalities in donor corneas to further optimize donor selection in eye bank. 18 In our study, we found the difference in endothelial cell density in the phakic group (2757.66328.5 cells/mm 2 ) and pseudophakic group (2225.56471.9 cells/mm 2 ) to be statistically significant (P,0.0001), but the difference in coefficient of variation and hexagonality was not significant. In another study, there were no statistically significant differences between the PC-intraocular lens corneas and the controls for any of the three major endothelial parameters (i.e., cell density, percentage of hexagonal cells, and coefficient of variation) studied.…”
Section: Discussionmentioning
confidence: 47%
“…16,17 Anterior Segment Optical Coherence Tomography has also been used to detect curvature abnormalities in donor corneas to further optimize donor selection in eye bank. 18 In our study, we found the difference in endothelial cell density in the phakic group (2757.66328.5 cells/mm 2 ) and pseudophakic group (2225.56471.9 cells/mm 2 ) to be statistically significant (P,0.0001), but the difference in coefficient of variation and hexagonality was not significant. In another study, there were no statistically significant differences between the PC-intraocular lens corneas and the controls for any of the three major endothelial parameters (i.e., cell density, percentage of hexagonal cells, and coefficient of variation) studied.…”
Section: Discussionmentioning
confidence: 47%
“…Donor corneas that are suitable for a transplantation are preoperatively examined for possible pathologies and anomalies using the inverted light microscopy and the optical coherence tomography (Quintin et al. 2021). As per our in‐house eye bank quality management protocol, the first step, is an examination of the cornea using a slit lamp microscope.…”
Section: Introductionmentioning
confidence: 99%
“…Another report from Germany has also found that the implementation of a quality management system and better management of contamination significantly reduces the rate of discarded donor tissue in the eye bank (27). Moreover, technical improvements, such as the application of anterior segment optical coherence tomograph providing a sterile screening method to identify corneal tissues, have further optimized donor selection and increased the utilization rate (28). Cornea arcus senilis was one of the causes of poor corneal quality as well as corneas with an endothelial cell count below 2,000 per mm 2 .…”
Section: Discussionmentioning
confidence: 99%